Analisis Framing Pemberitaan Kompas.com Mengenai Pembelajaran Jarak Jauh Paska Pandemi Covid-19 - Nurhusni Miftahulzanah, Siti (Da’watuna: Journal of Communication and Islamic Broadcasting, 2026)
This study analyzes the framing of Kompas.com news coverage regarding distance learning (Pembelajaran Jarak Jauh/PJJ) after the Covid-19 pandemic using Robert N. Entman’s framing model. Employing a qualitative content analysis of selected Kompas.com articles published from January to September 2023, the research explores how the media defines problems, diagnose causes, makes moral judgements, and recommends treatments related to PJJ. The findings reveal that Kompas.com consistently frames PJJ as both a challenge and an opportunity for educational transformation in Indonesia. The reporting highlights issues of infrastructure, digital literacy, and policy adaptation, while also appreciating innovation and collaboration, such as partnerships between educational institutions and industry. Kompas.com’s framing not only informs but also encourages public participation and policy improvement, demonstrating the strategic role of mass media in shaping public opinion and supporting educational reform in the post-pandemic era.